Impact of Gray Holes on Optimized Link State Routing Protocol - Sumathi, G; Aarthi, KC; Shanmugapriya, M (International Journal of Computer Sciences and Engineering, 2025)
Mobile Ad hoc Network (MANET) is a set of wireless devices that can move around freely and cooperate with each other in relaying packets without the support of any fixed infrastructure or centralized administration. The absence of any central administration or base station in the MANET makes the routing between nodes more complex compared to wireless networks. Since MANETs are useful in disaster and military operations, the need for the group communication is vital. Most of the routing protocols proposed for ad hoc networks assume a trusted, non-adversial environment and do not take security issues into account in their design. But in real time a MANET is vulnerable to attacks than a wired or infrastructure wireless network. This thesis investigates the security of Optimized Link State Routing protocol (OLSR), a well known routing protocol in MANET by identifying the impact of malicious nodes called Gray Holes on it. Thus, a security extension to address the gray hole attack in OLSR routing has been proposed and the solution is achieved in a simulation environment using NS-2 simulator.